2018
DOI: 10.1002/mabi.201800376
|View full text |Cite
|
Sign up to set email alerts
|

Dual Therapy Coating on Micro/Nanoscale Porous Polyetheretherketone to Eradicate Biofilms and Accelerate Bone Tissue Repair

Abstract: Defective osteogenesis and latent infections continue to be two major issues in the therapy of bone tissue regeneration. In this study, a unique hierarchically micro/nanoscale‐architecture is first proposed and produced on polyetheretherketone (PEEK). Besides, a “simvastatin‐PLLA film‐tobramycin microspheres” delivery system is subsequently fabricated to endow the PEEK implant with osteogenic and antibacterial capabilities. In vitro antibacterial evaluations confirm that the decorated PEEK scaffolds possess ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…sulfonation) are simple and costeffective, and can form a modified surface layer uniformly on complex surfaces without affecting the mechanical properties of the bulk matrix. 17,18 PEEK owns an aromatic molecular backbone with combinations of ketone and ether functional groups, rendering it resistant to attack by all substances apart from sulfuric acid. 19,20 Its sulfonation process has been widely studied and characterized as a potential resource of fuel cells membranes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…sulfonation) are simple and costeffective, and can form a modified surface layer uniformly on complex surfaces without affecting the mechanical properties of the bulk matrix. 17,18 PEEK owns an aromatic molecular backbone with combinations of ketone and ether functional groups, rendering it resistant to attack by all substances apart from sulfuric acid. 19,20 Its sulfonation process has been widely studied and characterized as a potential resource of fuel cells membranes.…”
Section: Introductionmentioning
confidence: 99%
“…hydroxyapatite) onto PEEK could also endow PEEK with bioactivity, 15,16 but the precise boundary and poor physical binding at the coating interface lead to a compromise in bonding strength of coating. 17 Surface chemical treatments (e.g. sulfonation) are simple and cost-effective, and can form a modified surface layer uniformly on complex surfaces without affecting the mechanical properties of the bulk matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly greater amount of mineralized matrix was observed in the presence of SIM release, with higher gene expression of ALP, Col-I, and BSP, such as observed in other investigations. 24,29 It was found that SIM released from the hydrogels maintained its osteogenic effect, as evidenced by the increased MC3T3-E1 cell mineralization. 24 SIM-loaded scaffolds increased the osteogenic potential of MC3T3-E1 and dental pulp cells, in a pathway that involves expression of the osteogenic mRNA gene, such as Col-I, ALP, BSP, and osteopontin.…”
Section: Discussionmentioning
confidence: 97%
“…24 SIM-loaded scaffolds increased the osteogenic potential of MC3T3-E1 and dental pulp cells, in a pathway that involves expression of the osteogenic mRNA gene, such as Col-I, ALP, BSP, and osteopontin. 8,29 PDLSC-based periodontal engineering has been extensively studied, and cell sheet strategy has been applied as a promising option to improve the regeneration of periodontal tissue. 30,31 Continuous cell sheets, with the preservation of cellular junctions and endogenous extracellular matrix, could provide a mimicking cellular microenvironment and showed the increased expression of cementogenic genes.…”
Section: Discussionmentioning
confidence: 99%